2018
DOI: 10.1016/j.tics.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Maturation Drives Memory from Generalization to Specificity

Abstract: During early ontogeny, the rapid and cumulative acquisition of world knowledge contrasts with slower improvements in the ability to lay down detailed and long-lasting episodic memories. This emphasis on generalization at the expense of specificity persists well into middle childhood and possibly into adolescence. During this period, recognizing regularities, forming stable representations of recurring episodes, predicting the structure of future events, and building up semantic knowledge may be prioritized ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
128
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(156 citation statements)
references
References 90 publications
(143 reference statements)
25
128
3
Order By: Relevance
“…Our findings on the relation between relational memory and mnemonic discrimination across the life span suggest that the maturation processes of relational memory and item mnemonic discrimination may occur in a relatively dissociable fashion, possibly because of the uneven maturation profiles across different hippocampal subfields (Keresztes et al, 2017(Keresztes et al, , 2018. In contrast, the decline in hippocampally dependent mnemonic processes, including relational memory and mnemonic discrimination, may occur in more unified manner at the tail end of life (Small et al, 2002).…”
Section: Relation Between Mnemonic Discrimination and Relational Bindingmentioning
confidence: 74%
“…Our findings on the relation between relational memory and mnemonic discrimination across the life span suggest that the maturation processes of relational memory and item mnemonic discrimination may occur in a relatively dissociable fashion, possibly because of the uneven maturation profiles across different hippocampal subfields (Keresztes et al, 2017(Keresztes et al, , 2018. In contrast, the decline in hippocampally dependent mnemonic processes, including relational memory and mnemonic discrimination, may occur in more unified manner at the tail end of life (Small et al, 2002).…”
Section: Relation Between Mnemonic Discrimination and Relational Bindingmentioning
confidence: 74%
“…These results demonstrate that the previously reported age effects on mnemonic discrimination using various tasks were not primarily due to factors such as the lack of motivation or age appropriateness of the task. Instead, the age‐related improvements in mnemonic discrimination are likely linked to neurobiological changes in intra‐ and extrahippocampal regions that are important for the development of pattern separation during childhood (Keresztes, Ngo, Lindenberger, Werkle‐Bergner, & Newcombe, ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that in the first few years of life, children may prioritize extracting schematic knowledge at the expense of encoding and recollecting past events with high specificity. The precedence of learning the general rules of the environment over remembering the specifics of past events may be advantageous, allowing infants and toddlers to build strong semantic knowledge of world (Keresztes et al, ; Newcombe, Lloyd, & Ratliff, ). An important question arising from this view is whether young children could prioritize encoding items with high specificity in circumstances in which the details of past experiences would be advantageous for subsequent remembering.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been suggested that in the first few years of life, children may prioritize extracting schematic knowledge at the expense of encoding and recollecting past events with high specificity. The precedence of learning the general rules of the environment over remembering the specifics of past events may be advantageous, allowing infants and toddlers to build strong semantic knowledge of world (Keresztes et al, 2018;Newcombe, Lloyd, & Ratliff, 2007). An important question arising from this view is whether young children could prioritize encoding items with high specificity in circumstances in which the details of past experiences would be advantageous for subsequent remembering.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that the previously reported age effects on mnemonic discrimination using various tasks were not primarily due to factors such as the lack of motivation or age appropriateness of the task. Instead, the age-related improvements in mnemonic discrimination are likely linked to neurobiological changes in intraand extrahippocampal regions that are important for the development of pattern separation during childhood (Keresztes, Ngo, Lindenberger, Werkle-Bergner, & Newcombe, 2018).…”
Section: The Influence Of Gain-loss Framing On Mnemonic Discriminationmentioning
confidence: 99%